Comparative and Global Framing of Enslavement - Conermann, Stephan; Rotman, Youval; Toledano, Ehud R.; Zelnick-Abramovitz, Rachel (Dependency and Slavery Studies, 2023)
Over the last two decades, social scientists, legal scholars, human rights activists, and historians, have sought common conceptual grounds in the study of enslavement, thus forging a new perspective that comprises historical and contemporary forms of slavery. This has also intensified awareness of enslavement as a global phenomenon. In this volume, the authors give tentative answers to the question on what global enslavement means.